Prevalence and genotypes of Giardia duodenalis in shelter dogs of southeastern Türkiye - AKYILDIZ, GÜRKAN (My University, 2023)
Giardia duodenalis is a protozoan parasite found in humans and several mammals. This parasite spreads worldwide and is generally recognized as a zoonotic agent being reported to be one of the most common causes of diarrhea in humans and animals. In this study, it was aimed to determine the prevalence and genotypes of G. duodenalis in shelter dogs in Diyarbakır province being located in the southeastern Anatolia region of Türkiye. NativeLugol method and nested polymerase chain reaction analyses of 100 fecal samples showed a prevalence of 3.00 and 4.00%, respectively. The prevalence was higher in females and in those younger than 1 year. Sequence analysis revealed the presence of zoonotic assemblage B, assemblage D and assemblage E. The detection of zoonotic assemblage B in this study suggests that dogs may be a reservoir for human giardiasis. Further molecular research is needed to determine the genotype diversity of Giardia as well as its possible role in the transmission of this parasite to humans.
Keywords: Veteriner Bilimleri; Klinik Öncesi Bilimler; Veteriner Parazitoloji; Sağlık Bilimleri; Veterinary Sciences; Pre-Clinical Sciences; Veterinary Parasitology; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Bitki ve Hayvan Bilimleri; VETERİNERLİK BİLİMLERİ; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); PLANT & ANIMAL SCIENCE; VETERINARY SCIENCES; At; Veterinerlik (çeşitli); Genel Veterinerlik; Equine; Veterinary (miscellaneous); General Veterinary; Giardia duodenalis; Nested polymerase chain reaction; Shelter dog; Türkiye